Dental Treatment Needs of Children with Disabilities - Yar Ali Rezay; Mahboobeh Shabzendedar; Behjat Almolook Ajami; Mohammad Asgary (Tabriz University of Medical Sciences, 2007)
Background and aims. Children and adolescents with disabilities appear to have poorer oral health than their non-disabled counterparts. The aim of this study was to assess the frequency and severity of oral diseases and treatment needs using world health organization criteria of caries, periodontal disease and malocclusions in a selected population of children with disabilities in Mashhad, Iran. Materials and methods. A randomized study on 1621 children aged 5-16 was conducted in 13 special schools by six examiners, using a mouth mirror, explorer and enough lighting. Results. The caries frequency of hearing impaired children (HI) was lower than those mentally retarded (MR) and visually impaired (VI) (DMFT: 2 ± 1.91 versus 2.27± 1.97 and 2.68 ± 2.30, respectively). MR children appear to have poorer oral hygiene and periodontal status than their otherwise disabled counterparts. Most children had class I malocclusion (57%). Conclusion. According to this study, an epidemiological survey followed by the implementation and evaluation of long-term public dental health care plan for children and adolescents with disabilities is highly recommended.